Peanut: Relationship, Arginine, and Cardiovascular Health - Sutrisno Adi Prayitno; Andalusia Trisna Salsabila; Devi Kartika Sari (Academic Letters, 2025)
Peanuts (Arachis hypogaea L.) are nutrient-dense legumes that play an important role in global food systems and human health. Beyond serving as an affordable source of energy and plant-based protein, peanuts are increasingly recognized as a functional food due to their rich content of unsaturated fatty acids, dietary fiber, minerals, phytosterols, and polyphenolic compounds associated with reduced cardiovascular disease (CVD) risk. Among these components, arginine—a semi-essential amino acid abundantly present in peanuts—has received considerable attention for its role in nitric oxide (NO) synthesis and vascular health. Arginine-derived NO is a key regulator of endothelial function, blood pressure, and platelet aggregation, and impaired NO bioavailability is closely linked to hypertension and atherosclerosis. Evidence from randomized controlled trials and meta-analyses published between 2020 and 2024 indicates that regular peanut consumption is associated with improvements in lipid profiles, inflammatory markers, and overall cardiometabolic health, particularly in individuals with metabolic disorders. The cardioprotective effects of peanuts are mediated through synergistic interactions between arginine, unsaturated fats, phytosterols, dietary fiber, and antioxidant compounds. Collectively, these findings support the inclusion of peanuts in balanced dietary patterns aimed at cardiovascular disease prevention.